The Influence of Advanced Enterprise Risk Management Implementation Analyses : The Role Of Environmental, Social and Governance Performances - Clarissa Maharani; Efa Yonnedi (Ilomata International Journal of Management, 2023)
The objective of this study is to investigate to which extend does Enterprise Risk Management Advanced (ERMADV) implementation impacts the firm performance and the moderated value by ESG performance. The assessment of ERMADV implementation level is conducted by using eight components derived from governance and firm operating activities with related measurements on Organization for Economic Cooperation and Development (OECD) principle and COSO ERM-Integrated Framework. Board Gender Diversity, Board of Commissioner Size, Firm Size, Leverage and Return on Equity (ROE) were further included in this study as control variables. This study focuses on the manufacture and mining industry registered on the Indonesia Stock Exchange website from year 2015 to 2021. The findings of this research indicate that ERMADV significantly affects firm performance and value. In addition, it is discovered that ESG plays a moderating influence. Furthermore, ESG suggests that an advanced ERM framework will prioritize risks associated with ESG-related aspects to find out whether or not it is resilient and integrated. As a result, this strategy will direct organizations in developing ethical decision-making strategies, thus, improving financial performance and firm value.